Explanation:
We multiply it to find the product
positive times positive = positive
positive times negative = negative
negative times positive = negative
negative times negative = positive
![(-(1)/(3))(-(1)/(3))= (1)/(9)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/7wxhzed0lvraop82ebkd964j546o0y9v8t.png)
Negative and negative is positive , so product is positive
![(-(1)/(3))((1)/(3))= -(1)/(9)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/yemy6x1papoa36z88a8hfqjd1krn63o8e4.png)
Negative and positive is negative , so product is negative
![((1)/(3))(-(1)/(3))= -(1)/(9)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/pcinsqq6peh1dtmvuame3u0lcnp9iczesb.png)
positive and negative is negative , so product is negative
![((1)/(3))((1)/(3))= (1)/(9)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ife8u6uevlisdsnzfpyx4susm77rj9ujy6.png)
positive and positive is positive , so product is positive